PRAYER ROOM QIBLA DIRECTION AT SCHOOL IN BUKITTINGGI : (Qibla Study in Junior High School and Senior High Schools Prayer Room) - Hendri Hendri (Fakultas Syari'ah dan Hukum UIN Walisongo, 2019)
Facing the qibla is one of the legal requirements in conducting prayer. The existence of the prayer room as a place of prayer in the school aims to fulfill the worship need for Muslim students and teachers, especially the midday prayer. However, the school owner never concerns towards qibla direction in School prayer room. This paper answers how the accuracy of the direction of the center of prayer at junior high school and senior high school in Bukittingg. By using library research method, researcher found that the method used is estimation method with concerning on Sunset direction, concerning on the buildings around it which defined in falak field as taqribi method. Furthermore, schools owners also used astronomy theory as the qibla direction method determination, such as compass qibla, Sun shadow and theodolite. Regarding to the qibla direction accuracy in Senior high schools and Junior high schools in Bukittinggi, researcher found there were two schools which were in accurate qibla direction, two schools which can be tolerated and eight remaining prayer rooms which were unforgivable due to incorrect method while implementing to decide the qibla direction.